Association of red blood cell distribution width and outcomes in patients with mantle cell lymphoma - Yi Miao; Xiao-Hui Zhou; Jing-Jing Guo; Qian Sun; Ke Shi; Jia‐Zhu Wu; Hua‐Yuan Zhu; Li Wang; Lei Fan; Wei Xu; Jian‐Yong Li (Cancer Medicine, 2019)
Abstract Red blood cell distribution width (RDW), which measures the range of variation of red blood cell volume, has been explored as a prognostic factor in multiple types of cancer. However, the role of RDW in mantle cell lymphoma (MCL), a rare type of non‐Hodgkin lymphoma with poor outcomes, remains to be determined. Therefore, we investigated the prognostic role of RDW in MCL. We found that 21 of 76 MCL patients (27.6%) had an abnormally elevated RDW (>15.7%). Abnormally elevated RDW was significantly associated with presence of B symptoms (P = 0.0020), elevated lactate dehydrogenase (LDH) (P = 0.0010), higher leukocyte count (P = 0.0345), higher simplified Mantle Cell International Prognostic Index (sMIPI) (P = 0.0194), and lower level of hemoglobin (Hb) (P < 0.0001). It was marginally associated with increased C‐reactive protein (P = 0.0862). RDW was significantly correlated with Hb level (r2 = 0.42) and LDH level (r2 = 0.19). 15.8% was determined as the best cutoff of RDW in predicting the survival outcome by the X‐tile software. Survival analysis revealed that high RDW (>15.8%) predicted shorter progression‐free survival (PFS) (hazards ratio [HR]: 3.14; P = 0.0005) and shorter overall survival (OS) (HR: 4.04; P < 0.0001). High RDW independently predicted both shorter PFS (P = 0.0493) and OS (P = 0.0118). RDW also improved the prognostic stratification based on sMIPI. In conclusion, our study identified RDW as a novel prognostic factor of clinical feasibility in the prognostication of MCL.